Russische Verben und Granularitaet - Marszk, Doris (Specimina philologiae Slavicae, 1996)
The real question of this work is: What is behind the phenomenon that the author names with the metaphor of graininess? Can different levels of granularity already be identified at the system level, or is granularity only apparent in the context? Is graininess even a lexical category of its own kind? One thing you might already (...) take for granted: granularity or granularity is a phenomenon that manifests itself above all in the verb and reaches the text via the verb. Therefore, the verb will be at the center of empirical investigations on granularity.